IITA 50 years annivesary media day - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Media Day is being organized to provide media partners the opportunity to visit IITA headquarters in Ibadan and learn firsthand about IITA’s efforts in addressing Africa’s most pressing challenges of hunger, malnutrition, poverty, and natural resource degradation. IITA was established in 1967 as the first African link in a global agricultural research network, later known as CGIAR, a partnership for a food-secure future. IITA works on improving the productivity of major African staples that include cassava, yam, maize, banana and plantain, cowpea, and soybean. In the last 50 years, we have been contributing to transforming agriculture in Africa through research for development. Working with various partners across sub-Saharan Africa, we improve livelihoods, enhance food and nutrition security, increase employment, and preserve natural resource integrity. To celebrate IITA’s 50th year of founding, we are organizing Media Day. Part of the day’s program is a tour of IITA’s research and development facilities, and interaction with IITA scientists working on various innovations and breakthroughs. To add value to the event, we organized a mini symposium that features a distinguished science communicator who would talk about his experiences in reporting about various topics in agriculture and science, including climate change, environment, health, and systems research, and a scientist-research administrator who would speak about what IITA will be looking at in the next 50 years.